Serological response and diagnostic value of recombinant candida cell wall protein enolase, phosphoglycerate kinase, and β-glucosidase - He, Zhengxin; Chen, Jing; Li, Wei; Cheng, Yan; Zhang, Hai-pu; Zhang, Li-na; Hou, Tian-wen (Frontiers in Microbiology, 2015)
There are no specific signs and symtoms for invasive candidiasis (IC), which makes its diagnosis a challenge. Efforts have been made for decades to establish serological assays for rapid diagnosis of invasive candidiasis, but none of them have found widespread clinical use. Using a systemic candiasis murine model, serological response to recombinant proteins of enolase (rEno1), phosphoglycerate kinase (rPgk1) and β-glucosidase (rBgl2) were evaluated and rEno1 was found to possess the strongest immunoreactivity, followed by rPgk1 and rBgl2. Likewise, IgG antibody titers to rEno1, rPgk1 and rBgl2 in the positive sera of proven IC patients were determined by ELISA. Results show anti-rEno1 antibody possesses the highest titer, followed by rPgk1 and rBgl2. Antibodies against rEno1, rPgk1 and rBgl2 were detected by ELISA tests in a group of 52 proven IC patients or 50 healthy subjects, The sensitivity, specificity, positive and negative predictive values were 88.5%, 90.0%, 90.2%, and 88.2% for anti-rEno1 detection, 86.5%, 92.0%, 91.8% and 86.8% for anti-rPgk1 detection, and 80.8%, 90.0%, 89.4% and 81.8% for anti-rBgl2 detection, respectively. The data clearly demonstrate that the recombinant proteins of Eno1, Pgk1 and Bgl2 are promising candidates for IC serodiagnosis. There’s great possibility that the recombinant Eno1 will be more applicable in serodiagnosis and vaccine research on account of its strong serological response.